Testing monitoring techniques for banded rails (Hypotaenidia philippensis assimilis) in coastal mangrove habitats of New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology at Massey University, Auckland, New Zealand - Mallinder-Capamagian, Indiana (Massey University, 2023)
The banded rail (Hypotaenidia philippensis assimilis) is a cryptic and elusive bird that inhabits wetlands and coastal mangrove forests in New Zealand, and is currently listed as 'At Risk - Declining' due to habitat loss and predation. Due to their elusive behaviour, monitoring this species is problematic using traditional methods, and as a result, little is known about their populations and distribution. Banded rails are considered a keystone species and an indicator of wetland health, making monitoring their populations and distribution crucial for effective wetland conservation and management. To address the lack of knowledge and understanding about banded rails, I tested the applicability and reliability of three monitoring methodologies in coastal mangrove habitats. Currently, there is no standardised methodology for monitoring banded rails, and it is unknown what techniques are best suited and the most reliable for this species. Presence/absence data were collected from 20 sites around the upper Waitematā Harbour using three main monitoring methodologies: footprint surveys, camera trapping, and call playback surveys. I fitted a range of generalised linear mixed models to the count data collected from all three monitoring techniques to identify factors affecting banded rail detection. Results showed that the size of mangrove habitats, the presence of freshwater, and substrate quality were significant predictors of banded rail footprint frequency. Additionally, freshwater, predators, and plot location were important factors affecting banded rail detection using camera traps. Footprint surveys were found to be a reliable and cost-effective method for detecting the presence of banded rails, while camera trapping provided valuable insights into their behaviour and habitat use. Although call-playback surveys were moderately effective for detecting the presence of banded rails, they may have limitations as a standalone technique. The results of this thesis have important implications for the conservation and management of wetlands in New Zealand. By testing and comparing various monitoring techniques, this research offers valuable insights into the ecology and behaviour of the banded rail, a keystone species and indicator of wetland health. The findings may inform the development of more effective monitoring protocols for banded rails and other cryptic wetland species, contributing to the existing literature on wetland ecology and conservation.
Keywords: 310307 Population ecology; 410404 Environmental management